2017
DOI: 10.1111/bor.12227
|View full text |Cite
|
Sign up to set email alerts
|

Late Pleistocene glaciations at Lake Donggi Cona, eastern Kunlun Shan (NE Tibet): early maxima and a diminishing trend of glaciation during the last glacial cycle

Abstract: 2017 (July): Late Pleistocene glaciations at Lake Donggi Cona, eastern Kunlun Shan (NE Tibet): early maxima and a diminishing trend of glaciation during the last glacial cycle.The Burhan Budai Shan in NE Tibet represents a key location for examining the variable influence of the midlatitude westerly and monsoonal circulations on late Quaternary glaciations in this sector of the Tibetan Plateau. Our study investigates the glacial history of mountains near Lake Donggi Cona (35°17 0 N, 98°33 0 E) using field mapp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 92 publications
0
14
0
Order By: Relevance
“…; Rother et al . ). It has been widely used to ascertain present and palaeo‐ELA depression (Porter ; Owen et al .…”
Section: Methodsmentioning
confidence: 97%
“…; Rother et al . ). It has been widely used to ascertain present and palaeo‐ELA depression (Porter ; Owen et al .…”
Section: Methodsmentioning
confidence: 97%
“…23‐20 cal. ka BP) probably correspond to fluvial deposits which were connected with youngest lateral moraines in the northern catchment dated to between 80 and 62 ka (Rother et al., 2017), enhanced by the melting process afterward.…”
Section: Resultsmentioning
confidence: 99%
“…However, the La Ji Shan, which is also located in the northeastern Tibetan Plateau, experienced a glacial advance during the LGM (Owen et al, 2003b;Murari et al, 2014). The annual precipitation in the La Ji Shan (200-400 mm; Owen et al, 2003b) is similar to that in the Bayan Har Shan (300-500 mm; Heyman et al, 2011) and Lake Donggi Cona (300-350 mm; Rother et al, 2017) areas, although the highest peak in the La Ji Shan (4898 m asl) is lower than that in the Bayan Har Shan (5267 m asl) and Lake Donggi Cona (5029 m asl) areas (Figure 1B). As such, other factors (e.g., relief and temperature) should be considered to determine the reason for the lack of the LGM glacial advance in the Bayan Har Shan and Lake Donggi Cona areas.…”
Section: Access Edited Bymentioning
confidence: 99%
“…Previous studies have shown that the Bayan Har Shan (Heyman et al, 2011) and Lake Donggi Cona (Rother et al, 2017) areas, which are located in the interior of the northeastern Tibetan Plateau (Figure 1A), were unglaciated during the Last Glacial Maximum (LGM). However, on the northeastern Tibetan Plateau, based on 10 Be exposure ages, glacial advance occurred during the LGM in some regions (e.g., Qilian Shan (Cui, 2017;Owen et al, 2003c) and the Anyemaqen area (Owen et al, 2003a).…”
Section: Access Edited Bymentioning
confidence: 99%
See 1 more Smart Citation